2022
DOI: 10.1186/s12884-022-05234-5
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care utilization during the COVID-19 pandemic: an online cross-sectional survey among Filipino women

Abstract: Background The COVID-19 pandemic resulted in unprecedented challenges to healthcare systems worldwide, including interruption of antenatal care services. The study aimed to determine the utilization of antenatal care services of Filipino women during the COVID-19 pandemic. Methods A cross-sectional study was conducted among postpartum women using an online self-administered survey in the Philippines from January 1 to March 31, 2022. The questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…The participants were well-versed in the significance of diagnostic procedures for feto-maternal monitoring, the necessity of iron and calcium supplements; thus reflecting a comprehensive understanding of the essential obstetric care required by them. This sentiment echoed the findings of a systematic review from South America [17] Another remarkable finding is that the awareness was put very well into practice by women in the study, which was similar to a cross-sectional study conducted in the Philippines, establishing prior pregnancy experiences as the positive predictors of adequate ANC [18]. This suggests a general adherence to the importance of seeking prenatal care, despite the challenges posed by any restrictive future health condition.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The participants were well-versed in the significance of diagnostic procedures for feto-maternal monitoring, the necessity of iron and calcium supplements; thus reflecting a comprehensive understanding of the essential obstetric care required by them. This sentiment echoed the findings of a systematic review from South America [17] Another remarkable finding is that the awareness was put very well into practice by women in the study, which was similar to a cross-sectional study conducted in the Philippines, establishing prior pregnancy experiences as the positive predictors of adequate ANC [18]. This suggests a general adherence to the importance of seeking prenatal care, despite the challenges posed by any restrictive future health condition.…”
Section: Discussionsupporting
confidence: 76%
“…Another remarkable finding is that the awareness was put very well into practice by women in the study, which was similar to a cross-sectional study conducted in the Philippines, establishing prior pregnancy experiences as the positive predictors of adequate ANC [ 18 ]. This suggests a general adherence to the importance of seeking prenatal care, despite the challenges posed by any restrictive future health condition.…”
Section: Discussionsupporting
confidence: 74%
“…Research by Kaphle et al, (2018) shows that as many as 87% of highly educated mothers use ANC. Educated mothers who can access and obtain information about their pregnancies have a better understanding of the benefits of ANC and are confident in making decisions (De Guzman et al, 2022). A similar study was conducted based on a health survey in Ethiopia that showed that >50% of highly educated mothers took advantage of ANC (Tsegaye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this increased risk, during the COVID-19 pandemic, pregnant women and their offspring might have experienced more difficulties in accessing clinical services, including monitoring, antenatal visits and pharmacological treatment, among others, due to several factors such as lockdown, travel restrictions and fear of infection. Prior studies have found an inadequate utilization of healthcare services and a delay in the initiation of antenatal care visits [ 6 , 7 , 8 ]. This fact might be of special relevance as the potential cause of increasing maternal mental health problems, such as clinical depression or anxiety, inadequate pharmacological treatment for chronic antenatal conditions and pregnancy undermonitoring.…”
Section: Introductionmentioning
confidence: 99%